Short-Term Stock Performance of Health Care Companies in Times of Viral Epidemics and Pandemics - Eugen Alberti; Tim Alexander Herberger; Manuela Ender (Atlantic Economic Journal, 2023)
The spread of Coronavirus Disease 2019 significantly influenced the global economy. Companies from the health care industry could emerge as potential winners in health crises, and their listed stocks could potentially outperform. For the first time in the English and German language literatures, this study investigates whether this occurred and which factors influenced the short-term stock price performance of companies from the health care industry during epidemics and pandemics. An event study of virus-related epidemics and pandemics from 2000 to 2020 was conducted. The results show that the stocks of companies from the health care industry tend to outperform the market during pandemics. The selection of the subindustry in the health care industry and the region of the stock markets significantly influenced abnormal returns. The results are especially relevant for investors seeking short-term trading opportunities but also provide implications for diversifying their portfolios during epidemics and pandemics.
Keywords: G11; G12; G15; 330; Portfolio choice; Pandemics; Epidemics; Event study; Health care industry